The Language in the Face of a New Social Reality of Women: Construction of Gender in Portavoza and Árbitra - Albitre Lamata, Paula (2021)
This essay analyses the relationships between language, society, and ideology. To this end, the evolution of two female professions (portavoza and árbitra) has been studied in three corpora of Spanish (CORDE, CREA, and CORPES XXI) and in the different editions of the dictionaries of the Academy. The results reflect that socio-historical changes that affected women throughout the twentieth-century condition the marking of the female gender, either through concordance or flexed form. From a lexicological perspective, this essay reflects on the epistemological assumptions of linguistic sexism that underlie the Spanish language and, more specifically, the category of gender.